"Modest Desires and Defiant Gestures": Representing Female Sexualities in Doreen Baingana's Tropical Fish: Tales out of Entebbe and Violet Barungi's Cassandra. Issue 1 (2nd January 2017) - Mtenje, Asante Lucy
Abstract : This article examines how Doreen Baingana in Tropical Fish: Tales out of Entebbe (2005) and Violet Barungi in Cassandra (1999) engage with aspects of female sexuality such as eroticism, desire, and sexual agency. I explore how these writers set these modes of being in intersectional relation with various patriarchal institutions. I focus on the different degrees of co-option and coercion, containment and escape associated with representations of female bodies and sexualities. In particular, I investigate how the authors' portrayal of female sexual agency contest at the same time as they reproduce received, normative "truths" about female sexualities.